Simultaneous Suppression of IMD3 and IMD5 in Space TWT by IMD3 and 2HD Signal Injection - Dongming Zhao; Huijuan Liu; Kewen Xia; Shi Li; Xiaoxu Shi (Active and Passive Electronic Components)
This paper presents a signal injection technology showing significant reductions in both 3rd-order and 5th-order intermodulation distortions (IMD3 and IMD5) in space traveling wave tube (STWT). By applying the IMD3 to the IMD5 ratio (TFR) as measures of location, the simultaneous suppressions of IMD3 and IMD5 in TWT are achieved by second harmonic distortion (2HD) and IMD3 injection. According to the research on theoretical analysis and computer simulation, the optimum amplitude and phase parameters of the injected signal for maximum simultaneous suppressions are obtained. Then an experiment system is established based on vector network analyzer, optimum TFR are 2.1 dB and 12.5 dB, respectively, by second harmonic and IM3 injection, and the output powers of IMD3 and IMD5 were decreased. TFR with IMD3 injection is smaller than that with second harmonic injection in STWT, and the experiment system is more straightforward and easy to operate. Thus, the IMD3 injection performs better than that of second harmonic injection to suppress IMD5s for the narrow-band STWT.